Cost-Effectiveness analysis of the culturally developed diabetes self-management education and support program among type 2 diabetes mellitus patients in Iraq - Ehab Mudher Mikhael; Siew Chin Ong; Saad Abdulrahman Hussain (Wolters Kluwer Medknow Publications, 2023)
Background: Diabetes mellitus (DM) is a chronic disease associated with a major economic burden on persons, health care systems, and countries. Diabetes self-management education and support (DSME(S)) programs are highly effective method in the management of T2DM patients. Therefore, this study aimed to determine the cost-effectiveness of the developed culturally-specific DSME(S) program regarding glycemic control, lipid profile, and body weight for Iraqi type 2 DM patients. Methods: A randomized controlled clinical trial design was used to assess the cost-effectiveness of the culturally-specific DSME(S) program from the perspective of health care providers. In the cost-effectiveness analysis (CEA), cost per patient and clinical outcomes over 6 months were compared between the intervention and control group. Incremental cost-effectiveness ratios (ICERs) were expressed as cost per unit improvement in glycosylated hemoglobin (HbA1c), fasting blood glucose (FBG), total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-C), high density lipoprotein- cholesterol (HDL-C), systolic blood pressure (SBP), diastolic blood pressure (DBP), and body weight. Results: The effectiveness of most outcomes was better in the intervention group compared with the control group. The ICER per unit improvement in HbA1c, SBP, DBP, serum TC, and TG levels was <1 of the minimum CET compared with the control group, thus meeting the definition of being highly cost-effective. Conclusion: The currently developed DSME(S) was cost effective method to improve glycemic control, blood pressure, TC, and TG for T2DM patients in Iraq.